Storytelling in the Media Convergence Age
XI, 252 p.
Keywords: Why do screen narratives remain so different in an age of convergence and globalisation that many think is blurring distinctions? This collection attempts to answer this question using examples drawn from a range of media, from Hollywood franchises to digital comics, and a range of countries, from the United States to Japan.